Reflection on Values of National Movement History as a Basis for Character Education - Wahyono, Effendi (TAWARIKH, 2016)
ABSTRACT: Nation and character building are two important aspects that proclaimed by the founding fathers of Indonesia in establishing the nation-state of Indonesia. Nation building, manifested by the successors in national economic development, can be said to be successful. National development focused on economic development led to the neglect of other sectors of development, namely the development of a national character. The waiver of character development has led to the disorientation of the values of Indonesian struggle, which is manifested in the precepts of âPancasilaâ (five basic principles of the Republic of Indonesia). Disorientation against the values of âPancasilaâ can be seen from the strengthening of hedonism, decreasing sting nationality and nationalism, the lack spirit of tolerance towards the differences in ideology, and the declining spirit of mutual cooperation. For that reasons, character education should be given back to the Indonesian people through both formal and informal education. Spirit, character, and values of the struggle must always be actualized in the present generation to be able to face the challenges of the time. Development is not only able to provide welfare of Indonesian people economically (physically), but also can produce Indonesian human in faith and fear of God Almighty, noble, healthy, knowledgeable, skilled, creative, independent, and become democratic and responsible citizens. Therefore, the values and fighting spirit of the founding fathers of Indonesia can be used in the reflections in developing the basics of character education.KEY WORDS: History of modern Indonesia, national movement, founding fathers of Indonesia, noble values, and character education.About the Author: Dr. Effendi Wahyono is a Senior Lecturer at the Faculty of Social and Political Sciences UT (Universitas Terbuka or Indonesia Open University), Jalan Cabe Raya, Pondok Cabe, Pamulang, Tangerang Selatan 15418, Banten, Indonesia. For academic interests, the author can be contacted via e-mail at: effendi@ut.ac.idHow to cite this article? Wahyono, Effendi. (2016). âReflection on Values of National Movement History as a Basis for Character Educationâ in TAWARIKH: International Journal for Historical Studies, Vol.7(2) April, pp.225-238. Bandung, Indonesia: Minda Masagi Press and UIN SGD Bandung, ISSN 2085-0980.Chronicle of the article: Accepted (March 30, 2016); Revised (April 15, 2016); and Published (April 28, 2016).